2018
DOI: 10.1007/s00330-017-5157-5
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Urogenital Radiology (ESUR) Guidelines: MR Imaging of Leiomyomas

Abstract: ObjectiveThe aim of the Female Pelvic Imaging Working Group of the European Society of Urogenital Radiology (ESUR) was to develop imaging guidelines for MR work-up in patients with known or suspected uterine leiomyomas.MethodsGuidelines for imaging uterine leiomyomas were defined based on a survey distributed to all members of the working group, an expert consensus meeting at European Congress of Radiology (ECR) 2017 and a critical review of the literature.ResultsThe 25 returned questionnaires as well as the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 51 publications
1
50
0
3
Order By: Relevance
“…Scheduling of MRI examination according to the menstrual cycle is not necessary. This agrees with the majority of authors in the literature [9].…”
Section: Schedulingsupporting
confidence: 93%
See 2 more Smart Citations
“…Scheduling of MRI examination according to the menstrual cycle is not necessary. This agrees with the majority of authors in the literature [9].…”
Section: Schedulingsupporting
confidence: 93%
“…It is recommended to achieve a moderately filled bladder, in line with previous ESUR guidelines [9][10][11].…”
Section: Bladdermentioning
confidence: 83%
See 1 more Smart Citation
“…There is no exposure to radiation and there is high contrast between structures in the female pelvis. Several studies have identified features of LMS on MRI utilizing intravenous contrast and diffusion‐weighted imaging (DWI), which can identify malignant lesions by a combination of intrinsic T 2 intermediate/hyperintensity, irregular margin, low apparent diffusion coefficient (ADC) value, hemorrhage, necrosis, avid enhancement, and/or rapid growth …”
mentioning
confidence: 99%
“…Several studies have identified features of LMS on MRI utilizing intravenous contrast and diffusion-weighted imaging (DWI), which can identify malignant lesions by a combination of intrinsic T 2 intermediate/hyperintensity, irregular margin, low apparent diffusion coefficient (ADC) value, hemorrhage, necrosis, avid enhancement, and/or rapid growth. [10][11][12][13][14][15][16][17][18][19][20][21][22] Based on these data, in late 2013 we created a preoperative protocol where we used MRI features to risk-stratify the appearance of fibroids in conjunction with our referring gynecologists, who used additional screening data such as total serum lactate dehydrogenase (LDH) 12 and endometrial biopsies to properly triage patients for appropriate fibroid treatment.…”
mentioning
confidence: 99%